A Virtual Resource Description and Discovery Model Based on Hybrid Granularity - Xijuan Su; Minghai Xu; Yu Xu; Yu Wang (Dianxin kexue)
The virtual resources description and discovery is an important premise for resources allocation in network virtual environment，however，there lacks efficient resource description method meeting the virtual resources characteristics in the current study. A new resource description mechanism was put forward which can describe virtual resources with different granularity by analyzing the virtual resources characteristics. And the efficiency of resource allocation has been promoted by the experiment using different granularity of resource description and this resource discovery method.